Self-Reliance in Crazy Rich Asians by Kevin Kwan (2013) - Sakuntala Ariesti Ruswandi; An Fauzia Rozani (English Language and Literature, 2022)
The purpose of this analysis is to expose the issue of self-reliance in the Novel Crazy Rich Asian by Kevin Kwan (2013). The issue of self-reliance refers to the way the character when the character gets bad treatment from the people but she is able to manage it. This analysis is text-based interpretation based on the concept of Self-reliance theory proposed by Elizabeth B. Hurlock. This analysis uses fictional devices such as character, plot (conflict) and setting that contribute in revealing the issue. The result of the study reveals the woman develops her self-reliance. It can be seen through behaviour and way of thinking.